Association Between Food Choices Motivators and Physical Activity in Body Image (dis)Satisfaction in Portuguese Adolescents - Dias, Sara Simões (2021)
Funding Information: This project is co-funded by the European Regional Development Fund, under the Portugal 2020 Program, through COMPETE 2020 (POCI-01-0145-FEDER-23557).